Lack of sources of information on the low participation of men using family planning: A Scoping review - Rizka Mardiya; Hirza Rahmita; Nurhidaya Fitria (Science Midwifery, 2022)
Family planning (henceforth; KB) is an attempt to control the number and spacing of children born. At present there are still many low participation of men in using family planning, where people always think that family planning only followed by women and men only as decision maker. The husband’s participation in family planning in Indonesia itself is still very low at around 1,3%. The factors that influence the use of contraception in men are vary, as for the factors that influence the use of contraceptive methods, namely the behavior of seeking contraceptive information. And men;s lack of access to information and services is a barrier to using contraceptive methods. Based on the background mentioned, it is important to conduct a study related to the lack information sources on male participation as family planning acceptors. The puspose of this scoping review is to find out the causes of the lack of information sources on the low interest of men to become family planning acceptors. The method used in the preparation of this scoping review used Arksey and O’Malley guideline the results obtained that the factors causing the low participation of men becoming a family planning acceptor is a factor. Sources of information (mass media, health promotion program) few men hear about contraception from health works and the lack of information about contraceptive services is a barrier for men to become family planning acceptors.